Effect of heat treatments on microstructural and mechanical characteristics of dissimilar friction stir welded 2198/2024 aluminum alloys. Issue 3 (1st February 2022) - Masoumi Khalilabad, Mahdi; Zedan, Yasser; Texier, Damien; Jahazi, Mohammad; Bocher, Philippe
Abstract: The 3 rd generation of aluminum–lithium (Al–Li) alloys provides a desirable combination of high mechanical properties and low density compared to their traditional counterparts, exempt of lithium. Therefore, providing a reliable joint between new and conventional aluminum alloys is crucial for making hybrid structures. The present study focuses on improving the mechanical properties of dissimilar AA2198/AA2024 joints using different heat treatments before and after welding. Tensile tests paired with digital image correlation (DIC) techniques and micro-hardness maps were performed to document the macro-scale and local mechanical behavior of the joints. As-welded joints demonstrated a similar yield strength, 30% lower than that of the base metals in T3 and T8 metallurgical states. As-welded joints failed at the AA2198 side in the heat affected zone (HAZ), parallel to the thermo-mechanically affected zone (TMAZ), region experiencing intense strain concentration and minimal hardness values. Post welding-heat treatments (PWHT) was found to successfully strengthen HAZ on the AA2198 side, without abnormal grain growth in the nugget and impairing the hardness properties on AA2024 side. This improvement in local mechanical properties on the AA2198 side was related to the re-precipitation of dissolved T1 (Al2 CuLi) and θ (Al2 Cu) during welding as characterized by differential scanning calorimetry (DSC) and microscopy analyses. However, PWHT joint variants demonstrated a reduction in total elongation and ultimate tensile strength due to intense strain localization on the AA2024 retreating side compared to a much more homogeneous strain distribution in the as-welded joints.